Impurity-driven formation of branched pores in porous anodic alumina. (September 2016) - Kim, Byeol; Youn, Yong; Park, Yi-Seul; Moon, Dal Nim; Kang, Kyungtae; Han, Seungwu; Lee, Jin Seok
Abstract: Understanding of pore formation in porous anodic alumina is prerequisite for realizing its potential applications in the field of nanofabrication. Here, we explored the impurity-driven pore formation of porous anodic alumina via a two-step anodization process in acid solution with various applied voltages. We varied the purity of Al foil, and found that the branching and bending of pores displayed by low-purity Al foils are originated from an electric-field imbalance that results from the presence of impurities. Also, the pore formation mechanism and characteristic geometry induced by the impurities within the Al foil were investigated using experimental and simulation models. Graphical abstract: